(untitled) (Pubmet, 2023)
In times of war raging on European soil, the academic community can help by doing what it knows best – documenting important evidence and publishing research. The experience of the Croatian Medical Journal (CMJ) editors during the Homeland War shows how a scientific journal can help during wartime (Marušić & Marušić, 2002). The CMJ published numerous scientific articles on various aspects of war (Marušić & Marušić, 2012; Marusic, Markulin, Lukic, & Marusic, 2006). To attract more authors to write about war and to improve the quality of the submissions CMJ editors introduced an authorhelpful prereview (Marusic & Marusic, 2001). CMJ editors worked with the authors to help them prepare their manuscripts until they were ready for an external peer review. Editorial staff working closely with authors formed the cornerstone of CMJ editors’ work and became a unique approach in the world of medical journals (Marušić & Marušić, 2002, 2022). In October 2022, the directors of the postgraduate doctoral program Translational Research in Biomedicine (TRIBE), decided to use that experience and together with the editorial board of the ST-OPEN journal, which is now led by the former editors of CMJ, launch the Giving Voice project to help Ukrainian authors write reports about the war in Ukraine. We named the project Giving Voice because we wanted to give a platform to voices that often are not heard loud enough, particularly those that do not belong to academic elites: students, refugees, vulnerable and marginalized groups, and others whose lives have been disrupted by war. In collaboration with the ST-OPEN editorial staff, we are inviting interested authors from Ukraine to send us their manuscripts. ST-OPEN is an interdisciplinary journal so we welcome contributions from all scientific fields. We will re-employ the author-helpful prereview. Our help will include assistance with study planning, statistics, writing, and English language editing to make the obtained data publishable. Other experts who would like to become a part of our network of mentors are more than welcome. All articles will go through a formal external review process, so we cannot guarantee that all will be accepted for publication, but we will do our best to make them publicationready. Although many projects are aimed at helping the academic community in Ukraine, to our knowledge, our approach is unique. Additional details about the Giving Voice project, already published articles, and similar projects are listed on the project website (Sapunar, 2022). As members of the academic community, we can make a difference within our professional realm. We should not only be a simple service for publishing articles but also, perhaps more importantly, agents of change for the scientific community. As directors of the TRIBE doctoral program, we aim to educate scientists to solve research problems and write reports about them. We should not only try to provide future scientists with knowledge and skills or gather them around the key values – we should also help create enlightened agents of change and equip them with leadership qualities accompanied by social and moral accountability (Frenk et al., 2010). We will extend the same efforts to the authors and mentors who decide to take part in the Giving Voice project.